Nano Hybrids Vol. 7 (Trans Tech Publications Ltd, 2014)
This periodical publishes research and review articles on hybrid nanomaterials such as inorganic-organic, inorganic-inorganic and organic-organic. It focuses on all aspects of nanoscience, nanotechnology and composites. Keywords: Synthesis and characterization of nanomaterials and composites, applications and modeling, Advances in composites and nanomaterials science, nanotechnology, nanobiology and nanobiotechnology